BIMBINGAN PERKAWINAN BAGI CALON PENGANTIN SIAP CEGAH STUNTING DI KANTOR URUSAN AGAMA KECAMATAN HAURGEULIS, INDRAMAYU - Abdur Rahim, Abdur Rahim; Islami, Bilat Nur; Arrasyid, Muhammad Ikhwan; Sidiq Al Fath, Imam Nur; Haekal, Muhammad; Sidiq, kholaif Aulia; Supriyatno, Supriyatno; Fadillah, Muhammad Haikal (Jurnal Abdimas Bina Bangsa, 2024)
This activity focuses on the high prevalence of stunting in Indonesia, which reached 24.4% in 2021. Stunting is a condition where children fail to grow due to chronic malnutrition, affecting their physical and cognitive development. In Haurgeulis Subdistrict, Indramayu, the issue of stunting is also a significant concern, necessitating preventive measures involving prospective couples. The marriage counseling program aims to increase knowledge and awareness among future spouses about the importance of health before and during pregnancy. The purpose of this activity is to understand the factors that contribute to stunting, the critical role of marriage counseling in preventing stunting, and the role of the Office of Religious Affairs (KUA) in providing marriage counseling to prospective couples. The method of implementing counseling involves a series of educational sessions with expert speakers. These sessions cover topics such as balanced nutrition, reproductive health, and family planning techniques. The activity also includes interactive discussions and Q&A to ensure participants' comprehension. The findings from the marriage counseling program for prospective couples to prevent stunting at the Office of Religious Affairs in Haurgeulis Subdistrict, Indramayu, highlight factors such as chronic malnutrition, often beginning during pregnancy, health issues, socioeconomic factors, and cultural practices. Additionally, government policies on providing nutritious food play a role. Marriage counseling plays a vital role in preventing stunting by raising awareness and knowledge about health and nutrition among future couples. The KUA holds a strategic role in providing marriage counseling to prospective couples. As the official body responsible for marriage, the KUA not only records marriages but also educates couples preparing for marriage